2021
DOI: 10.21608/jmr.2021.70288.1062
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Effects of Some Pollen Types on Hypopharyngeal and Acid Glands in Honeybee Workers (Apis Mellifera L.)

Abstract: Pollen had a wide range of effects on honey bee. Caged honey bee workers were used to determine the nutritional effects of four main types of pollen collected by honey bee colonies from the study area on the food consumption rates, the development of the hypopharyngeal gland (HPG) acini and acid gland (AG) sacs in honey bee workers. Additionally, chemical analysis of the selected pollen types was performed. Pollen diets were as follows: broad bean pollen, date palm pollen, clover pollen, maize pollen and mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The initial rise in consumption rates compared to the last recorded ones for both diets can be attributed to the progressive mortality in caged individuals. Eshbah et al (2021) have observed that diet consumption was highest in day 6 for old bees across all diets. Diets consumption gradually decreased from day 9 for old bees till the end of the experiment No doubt that, supplementary nutrition has a vital role in preserving survival rates.…”
Section: Discussionmentioning
confidence: 82%
“…The initial rise in consumption rates compared to the last recorded ones for both diets can be attributed to the progressive mortality in caged individuals. Eshbah et al (2021) have observed that diet consumption was highest in day 6 for old bees across all diets. Diets consumption gradually decreased from day 9 for old bees till the end of the experiment No doubt that, supplementary nutrition has a vital role in preserving survival rates.…”
Section: Discussionmentioning
confidence: 82%
“…Also, workers fed on mixed pollen diet had the best average acinal surface area of HPG followed by those fed on broad bean pollen and corn pollen with similar degrees then followed by those fed on date palm and maize, respectively. Whereas bees fed on sugar solution only (control) had the lowest acinal surface area of HPG compared with other pollen diets, with statistically significant differences (Eshbah et al, 2021). also, Lan et al (2021) Pollen sources have significant effects on the stinger apparatus in worker honey bees.…”
Section: Discussionmentioning
confidence: 94%
“…This finding suggests that the pollen source can influence the size and development of the venom sac parameters in honey bees. Also, Hosafy et al, (2021) reported that feeding honey bees on a mixture of pollen diet and a broad bean pollen diet resulted in better results than others in the development of HPG and AG.…”
Section: Venom Sac Length and Widthmentioning
confidence: 98%
See 1 more Smart Citation